Trajectories and risk factors of fatigue following colorectal cancer diagnosis - Li, Xiaoyin; Hoogland, Aasha I.; Small, Brent J.; Crowder, Sylvia L.; Gonzalez, Brian D.; Oswald, Laura B.; Sleight, Alix G.; Nguyen, Nathalie; Lorona, Nicole C.; Damerell, Victoria; Komrokji, Khaled R.; Mooney, Kathi; et al. (Colorectal disease, 2023)
Aim This study sought to identify groups of colorectal cancer patients based upon trajectories of fatigue and examine how demographic, clinical and behavioural risk factors differentiate these groups. Method Patients were from six cancer centres in the United States and Germany. Fatigue was measured using the fatigue subscale of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) at five time points (baseline/enrolment and 3, 6, 12 and 24 months after diagnosis). Piecewise growth mixture models identified latent trajectories of fatigue. Logistic regression models examined differences in demographic, clinical and behavioural characteristics between fatigue trajectory groups. Results Among 1615 participants (57% men, 86% non-Hispanic White, mean age 61 ± 13 years at diagnosis), three distinct groups were identified. In the high fatigue group (36%), fatigue significantly increased in the first 6 months after diagnosis and then showed statistically and clinically significant improvement from 6 to 24 months (P values < 0.01). Throughout the study period, average fatigue met or exceeded cutoffs for clinical significance. In the moderate (34%) and low (30%) fatigue groups, fatigue levels remained below or near population norms across the study period. Patients who were diagnosed with Stage II−IV disease and/or current smokers were more likely to be in the high fatigue than in the moderate fatigue group (P values < 0.05). Conclusion A large proportion of colorectal cancer patients experienced sustained fatigue after initiation of cancer treatment. Patients with high fatigue at the time of diagnosis may benefit from early supportive care.